Radiation Therapy (RT) target determination for irradiation of bone metastases with soft tissue component: Impact of multimodality imaging - Omer Sager; Ferrat Dincoglan; Selcuk Demiral; Murat Beyzadeoglu (Journal of Surgery and Surgical Research - Peertechz Publications, 2021)
Objective: Management options for bone metastases include surgical interventions, Radiation Therapy (RT), chemotherapy and other systemic and targeted agents. RT as external beam irradiation and by use of stereotactic radiotherapeutic approaches has been utilized for safe and efficacious management of bone metaseses. In the context of bone metastases with extraosseous soft tissue mass, the issue of irradiation target definition is a critical component of radiotherapeutic management for successful treatment. Herein, we evaluated target definition for irradiation of bone metastases with soft tissue component by incorporation of multimodality imaging. Materials and methods: RT target definition for irradiation of bone metastases with soft tissue component was assessed in this study.  Results: Patients receiving palliative irradiation for bone metastases with soft tissue component were assessed for target volume determination. Treatment planning process was performed using the Elekta Precise treatment planning system (Elekta, UK) at our department. Definition of ground truth target volume was performed by the board certified radiation oncologists following meticulous evaluation, colleague peer review, collaboration, and ultimate consensus. Synergy (Elekta, UK) LINAC was used for irradiation. Comparative assessment in our study revealed that ground truth target volume was identical with target volume definition by CT-MR fusion based imaging.  Conclusion: Incorporation of multimodality imaging in target definition of bone metastases with soft tissue component may be utilized for improving the accuracy for precise RT despite the need for further supporting evidence.